The Genetics of Resistance to Gastrointestinal Parasites in Florida Native Sheep - Zaira Magdalena Estrada Reyes; D. Owen Rae; Carol Postley; Raluca G. Mateescu (EDIS, 2021)
This 3-page publication provides a brief overview of resistance to gastrointestinal nematode infections in Florida Native sheep. Written by Zaira M. Estrada Reyes, Owen Rae, Carol Postley, and Raluca G. Mateescu, and published by the UF/IFAS Department of Animal Sciences, August 2020.